Sternal Reconstruction with the Omental Flap—Acute and Late Complications, Predictors of Mortality, and Quality of Life - Kolbenschlag, J.; Hörner, C.; Sogorski, A.; Goertz, O.; Ring, A.; Harati, K.; Lehnhardt, M.; Daigeler, A. (Journal of Reconstructive Microsurgery, 2018)
Background The omental flap is a reliable flap for the coverage of sternal defects. However, little is known about the predictors of mortality and the long-term outcome in such patients.Methods We, therefore, performed a retrospective study from 2002 to 2013, including all patients who underwent sternal reconstruction with the omental flap.Results A total of 50 patients were identified and mean follow-up was 3.8 years. Patient data was collected from the charts and 14 patients were available for telephone interviews. The majority of patients suffered from deep sternal wound infections. There was no complete flap loss and an overall success rate was 96%. In-hospital mortality was 14% and overall survival over follow-up was 50%. Significant predictors of mortality were age > 65, American Society of Anesthesiologists' status, defect size, prolonged ventilation, and the need for tracheotomy. Postoperative quality of life was reduced compared with other cohorts, especially with regard to bodily function. Pain was also a major problem for most patients along with herniation.Conclusion The omental flap is a safe option even in patients with severe comorbidities. However, based on the data in this study, we would recommend the omental flap as a reserve option rather than first-line treatment for sternal defects.
Keywords: sternal reconstruction; omental flap; sternum; outcome; quality of life; local flap